Precision Obesity Treatments Including Pharmacogenetic and Nutrigenetic Approaches. (July 2016) - Solas, Maite; Milagro, Fermin I.; Martínez-Urbistondo, Diego; Ramirez, Maria J.; Martínez, J. Alfredo
Abstract : Five pharmaceutical strategies are currently approved by the US FDA for the treatment of obesity: orlistat, lorcaserin, liraglutide, phentermine/topiramate, and bupropion/naltrexone. The most effective treatment seems to be the combined administration of phentermine/topiramate followed by lorcaserin and bupropion/naltrexone. In relation to the management of excessive weight, other aspects also need to be considered, including comorbidities accompanying obesity, drug interactions, and the risk of negative collateral effects, as well as individualized treatments based on the genetic make-up. This review aims to provide an overview of the approved anti-obesity drugs and newer molecules that could affect different targets in the central nervous system or peripheral tissues, the molecular mechanisms, emerging dietary treatments and phytogenic compounds, and pharmacogenetic/nutrigenetic approaches for personalized obesity management. Trends: Obesity prevalence is a worldwide health burden, with many associated comorbidities, and needs to be precisely tackled. New drugs and novel medicine approaches are currently being investigated to fight against excessive weight gain, but only a few are on the market. Understanding the factors involved in body weight homeostasis, such as appetite and energy expenditure control, will be necessary to design newer suitable treatments against obesity. Pharmacogenetic and nutrigenetic strategies will contribute to a more individualized management of obesity. New dietary approaches based on different macronutrient distributions and molecules derived from bioactive compounds in plants could help to manage energy metabolism disturbances.